Comparing the Westmead Posttraumatic Amnesia Scale, Galveston Orientation and Amnesia Test, and Confusion Assessment Protocol as Measures of Acute Recovery Following Traumatic Brain Injury. Issue 3 (May 2021) - Spiteri, Courtney; Ponsford, Jennie; Jones, Harvey; McKay, Adam
Abstract : Background: The duration of the acute period of recovery following traumatic brain injury (TBI) remains a widely used criterion for injury severity and clinical management. Consensus regarding its most appropriate definition and assessment method has yet to be established. Objective: The present study compared the trajectory of recovery using 3 measures: the Westmead Post-Traumatic Amnesia Scale (WPTAS), the Galveston Orientation and Amnesia Test (GOAT), and the Confusion Assessment Protocol (CAP). Patterns of symptom recovery using the CAP were explored. Participants: Eighty-two participants with moderate to severe TBI in posttraumatic amnesia (PTA) on admission to an inpatient rehabilitation hospital. Design: Prospective longitudinal study. Outcome Measures: Length of PTA (days), agreement between measures (%, κ coefficient), and pattern of symptom recovery. Results: Participants emerged from PTA earliest on the CAP followed the GOAT, and last on the WPTAS. There was good agreement between the CAP and the GOAT as to PTA status, but both tests had poor agreement with the WPTAS. Of patients considered out of PTA on the CAP, the majority exhibited signs of amnesia on the WPTAS and one-third had clinical levels of agitation. Conclusion: The WPTAS identifies a later stage of PTA recovery that requires specialized management due to ongoing amnesia and agitation. The CAP and the GOAT are less sensitive to this extended period of PTA.